Effectiveness of a Culturally Tailored Diabetes Self-Management Program for Chinese Americans - Sun, Angela C. (Diabetes Educ, 2012)
PURPOSE: The purpose of the study was to test the feasibility and efficacy of a diabetes self-management and education program for Chinese Americans in a support group format. The rationale for the study was to create culturally appropriate diabetes education and management programs in response to the growing diabetes prevalence among Chinese Americans. The investigators hypothesized that participants will have improved diabetes knowledge and practices, hemoglobin A1C, and social support. The study objectives were at least: 50% will have significant improvements in diabetes knowledge and practice activities, 30% of participants will have significant improvements in A1C, and 50% will report a gain in emotional support. METHODS: The program consisted of 12 90-minute diabetes education and support group sessions offered in a medical office setting. The sample included 23 Chinese Americans with either type 1 or type 2 diabetes. Using a single-group, pre-post test design, A1C and diabetes knowledge were assessed at baseline and 6 months. Data were collected through clinical assessments and written questionnaires. RESULTS: The results indicated high attendance and statistically significant increases in glycemic control and diabetes knowledge. Statistically insignificant differences were shown in diabetes management practices. Secondary outcomes assessed participants’ perceived diabetes management and emotional and social support. CONCLUSIONS: Diabetes Self-Management: A Cultural Approach (DSMCA) support group model demonstrates that a culturally tailored support group utilizing a community-based participatory research approach is an effective format to improve diabetes self-management skills among Chinese Americans. The program can be adapted for other ethnic populations. The efficacy of the intervention can be further tested in larger randomized trials.